Pengaruh Model Pembelajaran Kooperatif Tipe Time Token terhadap Hasil Belajar Fisika Siswa - Fifiyanti; Amiruddin Hatibe; I Wayan Darmadi (Universitas Tadulako, 2021)
This study aims to see whether there is an effect of the time token type cooperative learning model on the physics learning outcomes of seventh grade students of SMP Negeri 1 Banawa Tengah. The type of research used is a quasi-experimental design with